Plan de mantenimiento y conservación de los equipos y materiales del aula de práctica docente - Chuqui Rosero, Gina Gabriela (2015)
This research work aims to assess the significance of the correct use of equipment and materials in the teaching practice classroom of the Technical University of Cotopaxi in Latacunga city, it is applying adequate alternatives to maintain in good conditions each of hearing and vision interactive technological resources such as the interactive digital screens that there are in this lab. In the process of research surveys to students and teachers were applied;; interviews with university authorities to establish institutional educational reality, with the results achieved it is proposed the Design of Maintenance and Conservation Plan for the authorities together with the educational community empowers people responsible and accountable in the use and application of classroom teaching practice to avoid problems with the operation in order to avoid drawbacks in the correct operation…